Foreign direct investment and Renewable energy developmentin sub-Saharan Africa: Does governance quality matter? - Toyo Amegnonna Marcel Dossou; Emmanuelle Ndomandji Kambaye; Simplice Asongu; Alastaire Sèna Alinsato; Mesfin Welderufael Berhe; Kouessi P. Dossou (African Governance and Development Institute (AGDI), 2023)
Existing studies have been separated, considering the foreign direct investment (FDI) and renewable energy development (RE) nexus and the governance quality- renewable energy development relationship. However, the study regarding the moderation of governance quality on the FDI-renewable energy nexus is quite scarce. To fill the gap in the literature, the study therefore examines the moderation of governance quality on the influence of FDI on (RE) in 37 sub-Saharan African economies over the period 1996-2020. To achieve this goal, the panel corrected standard errors (PCSE) estimation technique has been adopted. The results show that FDI has a positive and significant effect on RE, meaning that an increase in foreign direct investment could lead to a 0.05 increase in RE. Moreover, the results unveil that governance quality is positively and significantly associated with RE. This means that a unit increase in control of corruption, governance effectiveness, rule of law, and voice and accountability leads to a 9.64, 9.10, 10.10 and 9.08 increase unit in the renewable energy sector, respectively. Most importantly, the results indicate that the interaction between FDI and governance quality has a positive and significant effect on RE. Policy implications are discussed based on the findings revealed by this study.
Keywords: 330; Foreign direct investment; governance quality; renewable energy development; sub-Sharan Africa